2014
DOI: 10.1117/1.oe.53.9.094102
|View full text |Cite
|
Sign up to set email alerts
|

Phase error elimination considering gamma nonlinearity, system vibration, and noise for fringe projection profilometry

Abstract: Abstract. Fringe projection profilometry (FPP) using a digital video projector is widely used for three-dimensional shape measurement. However, the gamma nonlinearity, system vibration, and noise cause the captured fringe patterns to be nonsinusoidal waveforms and have a grayscale deflection from their true value. This leads to an additional phase measurement error for a general phase-shifting algorithm. Based on the theoretical analysis, we propose a method to eliminate the phase error considering two factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The 'gold standard' in ML algorithms for images is CNN, which is a network-based ML, but compared with neural networks with similar sized layers, CNNs have fewer connections and parameters, and thus are easier to train [154]. Moreover, CNNs are able to capture the nonlinearity in datasets; non-linearity is commonly found in images, such as photographs and electron micrographs, because of a number of elements [155][156][157][158][159][160]. Two studies have demonstrated the feasibility of utilising CNN for EHD process monitoring.…”
Section: Machine Learning For Image Classificationmentioning
confidence: 99%
“…The 'gold standard' in ML algorithms for images is CNN, which is a network-based ML, but compared with neural networks with similar sized layers, CNNs have fewer connections and parameters, and thus are easier to train [154]. Moreover, CNNs are able to capture the nonlinearity in datasets; non-linearity is commonly found in images, such as photographs and electron micrographs, because of a number of elements [155][156][157][158][159][160]. Two studies have demonstrated the feasibility of utilising CNN for EHD process monitoring.…”
Section: Machine Learning For Image Classificationmentioning
confidence: 99%
“…Phase extraction based on such fringe patterns has a nonlinear error, which requires a phase error elimination algorithm. [6][7][8][9][10][11] At present, the measurement resolution of fringe projection profilometry can generally reach 1/10,000 of the measurement field of view. 12,13 In the projection moiré method, a two-stage imaging and receiving system was proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Vibration is inevitable and sporadic in factories, especially forging factories, and may cause fatal errors to the optical systems. For an inspection system using phase-shifting profilometry (PSP), vibration may cause mistakes or losses in the reconstructed 3D data [2], which will affect the inspection results and confuse the following procedures. This kind of vibration is hard to prevent or predict, and the only economical and feasible solution is to detect if a vibration occurs and then try to compensate the motion error caused by the vibration.…”
Section: Introductionmentioning
confidence: 99%